PENINGKATAN MINAT DAN HASIL BELAJAR TEMATIK DENGAN MENGGUNAKAN MEDIA GAMBAR SISWAKELASI SDIT NURUL IKHLAS PADANG - Hidayati Azkiya; Mardiana Mardiana (Cerdas Proklamator, 2019)
This study aims to describe the interests and learning outcomes of students by using picture media in learning theme 1 of subtheme 3 in class I SDIT Nurul Ikhlas Padang ". This type of research is Classroom Action Research. The instrument for data collection was obtained through observation of students' interest sheets, teacher observation sheets and learning achievement tests. The results of the study are the first through the use of media interest pictures and student learning outcomes have increased, which can be seen in the observation sheet that has been filled out by the observer teacher where in the first cycle the acquisition of student learning outcomes has increased namely the average value in the first cycle 57 with mastery learning 71% increased to 72.72 in the second cycle with 88% completeness. The conclusion of this research is that through media images can increase student interest and learning outcomes.